Local competences in the field of public safety (Euro-Latin American Journal of Administrative Law, 2014)
The author intends to highlight the importance that has the local character of the police power in matters of public safety; especially in a particularly sensitive matter for the human person. Thus it makes it especially attending the complex Argentine federal system, in which various organs and entities (national, provincial and municipal) must live together sharing a similar public role.